Unlocking the Mysteries of Academic Writing: A Corpus-based Analysis of Lexical Bundles in L2 English for Engineering Students - Barbara Wing Yee Siu; Muhammad Afzaal; Hessah Saleh Aldayel; Samantha Curle (SAGE Open)
This study examines the use of lexical bundles in reports produced by university-level L2 English writers in civil and environmental engineering (CEE). The corpus consists of 119 reports, and the study compares the use of different types of lexical bundles (3-word, 4-word, and 5-word) in high-scoring and low-scoring papers. The results show that high-scoring papers use a wider range of lexical bundles, and that the use of lexical bundles varies by discipline. The study also identifies specific features of the lexical bundles that contribute to score differences. The findings suggest that teaching lexical bundles and vocabulary can improve the academic writing of engineering students. The paper concludes by calling for further research on the impact of formulaic expressions on attainment scores in L2 writing.